ANALISIS PREFERENSI PENGUNJUNG KAWASAN WISATA GILI MENO KABUPATEN LOMBOK UTARA - Emilia Septiani; Budi Santoso; Mulyadi Mulyadi; Muhdin Muhdin (Distribusi - Journal of Management and Business, 2019)
The purpose of this research is to determine visitor preference of tourism area in Gili Meno, North Lombok Regency. As tourist preferences to Gili Meno divided into 3 preferences, i.e. the preference based on tourist attraction, accomodation and accessibility. Data collection method used in this research is sample survey. Sampling technique in this research use accidental sampling with amount of sample counted 50 people. The analytical tools used in this research is descriptive statistics with frequncy tables. The result of this study showed that: in term of tourist attraction the visitor preferred scenery and for as tourism activity they preferred snorkeling; in term of accomodation they preferred homestay and the place having a meal they preferred restaurant; accessibility preferences towards tourist sites is the ease of reaching the location and in term of transportation they preferred bicycle. Especially for accessibility, improvement the schedule departure of the boat to Gili Meno are needed.